Studi Kasus Identifikasi dan Penanganan Kasus HIV/AIDS Di Kota Salatiga - Yoku, Enjelina Rosa Pebrianti (Indonesian Academia Health Sciences Journal, 2020)
Objective:  This study aims to see how Salatiga’s goverment identificaton and they handles HIV/AIDS casesMethods:  This study applies qualitative method by using Single Case Embedded Study Results:  The results of this study showed that there are differences in the role of each institution that is Commission on AIDS, non-governmental organizations, health facilities, and citizen care AIDS contributes to the identification and handling of HIV/AIDS cases in the city of Salatiga besides the implementation of the program and identify the prevention of HIV/AIDS in Salatiga City refers to the local regulation of the city of Salatiga.Conclusion:  The identification and handling of HIV/AIDS cases in Salatiga is conducted referring to local regulation of the city of Salatiga  by integrating with hospitals, health centers, NGOS and key populations.